Security constrained augmentation for transmission system considering preferences of market players on expansion options - Hesamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (Curtin University, 2007)
This paper presents a new approach for transmission expansion planning in unbundled electricity industry. The approach considers the power market and technical criteria for selecting the most effective expansion options. Perfect competition, a stable electricity market, and a lower price of electricity at different market players' locations have been addressed in the proposed methodology. Reliability criteria have been considered in terms of transmission system security and sustainable load serving. To consider the preferences of market players for different expansion options, firstly, importance degree of market players are determined based on a digitised band. Then a fuzzy linguistic variable is assigned to the preference of each market player to the transmission options. Finally, the quantified linguistic variables are used to weight planning criteria and select the final plan. The results of applying the proposed methodology to the introduced case study are very promising.